2016
DOI: 10.4328/jcam.3292
|View full text |Cite
|
Sign up to set email alerts
|

Do Local Anesthetics Containing Epinephrine Affect Blood Pressure in the Elderly?

Abstract: Anahtar KelimelerDental; Lokal Anestezik; Epinefrin; Yaşlı; Kan Basıncı Abstract Aim: Dental procedures are often performed under local anesthesia. Vasoconstrictors added to local anesthetics might have unwanted effects in the elderly and in patients with comorbid diseases. The aim of this study was to evaluate the effects of local anesthetics containing epinephrine on blood pressure in elderly patients undergoing dental procedures. Material and Method: The study included 479 patients (age, 67.37±6.62) who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Hypertension has roughly constant prevalence among women while diabetes is the third most prevalent disease among men in the US [7]. The American Heart Association has reported that the prevalence of hypertension is 52% among both men and women aged between 55 and 64 years; 63.9% and 70.8%, respectively, among men and women aged between 65 and 74 years; and 72.1% and 80.1%, respectively, among men and women aged ≥75 years [8]. In our study, diabetes and hypertension were the most common chronic diseases among women.…”
Section: Resultsmentioning
confidence: 99%
“…Hypertension has roughly constant prevalence among women while diabetes is the third most prevalent disease among men in the US [7]. The American Heart Association has reported that the prevalence of hypertension is 52% among both men and women aged between 55 and 64 years; 63.9% and 70.8%, respectively, among men and women aged between 65 and 74 years; and 72.1% and 80.1%, respectively, among men and women aged ≥75 years [8]. In our study, diabetes and hypertension were the most common chronic diseases among women.…”
Section: Resultsmentioning
confidence: 99%